Granulomatous Foreign-Body Reactions to Permanent Fillers: Detection of CD123+ Plasmacytoid Dendritic Cells. (February 2015) - Kadouch, Jonathan A.; Vos, Wim; Nijhuis, Erik W. P.; Hoekzema, Rick
Abstract : Background: Soft-tissue augmentation with permanent fillers can lead to severe granulomatous foreign-body reactions (GFBRs), but the immune pathomechanism of this complication is still unknown. We performed conventional histologic examination and immunostaining for plasmacytoid dendritic cells (pDCs) in skin sections from patients with GFBR to 4 permanent filler agents, which have been widely used in recent decades. Methods: Twenty-one skin biopsies were studied from 19 patients with GFBR to polyalkylimide 4% gel (PAIG, n = 10), polyacrylamide 2.5% gel (PAAG, n = 2), hydroxyethyl methacrylate/ethyl methacrylate in hyaluronic acid (HEMA/EMA, n = 4), or liquid injectable silicone (n = 5). GFBRs were analyzed in hematoxylin and eosin stained sections and pDCs detected using CD123 antibodies. Anti-CD11c immunostaining was performed for comparison. Results: Grading of the inflammatory infiltrates observed histologically did not correlate with the clinical features of inflammation. Immunostaining for CD123 did not detect pDCs in 8 of 10 polyalkylimide gel, 1 of 2 polyacrylamide gel, and the 5 liquid injectable silicone biopsies. In contrast, all 4 HEMA/EMA biopsies contained collections of pDCs in lymphocytic infiltrates close to filler particles and adjacent sarcoidal granulomas. Conclusions: Our data suggest that pDCs contribute to the sarcoidal granulomas associated with injected HEMA/EMA. Recruited pDCs may exert their pro-inflammatory effects by the release of interferon-α at the site of these filler deposits.